2021
DOI: 10.1002/mrm.29059
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional simultaneous brain mapping of T1, T2, and magnetic susceptibility with MR Multitasking

Abstract: Purpose To develop a new technique that enables simultaneous quantification of whole‐brain T1, T2, T2∗, as well as susceptibility and synthesis of six contrast‐weighted images in a single 9.1‐minute scan. Methods The technique uses hybrid T2‐prepared inversion‐recovery pulse modules and multi‐echo gradient‐echo readouts to collect k‐space data with various T1, T2, and T2∗ weightings. The underlying image is represented as a six‐dimensional low‐rank tensor consisting of three spatial dimensions and three tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 86 publications
0
28
0
Order By: Relevance
“…Eight subjects (aged 24-67 y, three females) without known brain abnormalities were recruited. MT 36 and our pilot study shown in Supporting Information Appendix S1, Section C), SR period (the temporal resolution of dynamic T 1 ∕T * 2 mapping) is approximately 1.2 s, containing 60 segments at time points varying from 19.30 to 1160 ms, flip angle = 10 • , total time = 7.6 min. Single dose (0.1 mmol/kg of body weight) of CA (Gadavist; Bayer Schering Pharma, Berlin, Germany) was administered through antecubital intravenous access 1.5 min into the scan at the rate of 3.0 mL/s, followed by a 20 mL saline flush at the same rate.…”
Section: Healthy Volunteer Studymentioning
confidence: 87%
See 1 more Smart Citation
“…Eight subjects (aged 24-67 y, three females) without known brain abnormalities were recruited. MT 36 and our pilot study shown in Supporting Information Appendix S1, Section C), SR period (the temporal resolution of dynamic T 1 ∕T * 2 mapping) is approximately 1.2 s, containing 60 segments at time points varying from 19.30 to 1160 ms, flip angle = 10 • , total time = 7.6 min. Single dose (0.1 mmol/kg of body weight) of CA (Gadavist; Bayer Schering Pharma, Berlin, Germany) was administered through antecubital intravenous access 1.5 min into the scan at the rate of 3.0 mL/s, followed by a 20 mL saline flush at the same rate.…”
Section: Healthy Volunteer Studymentioning
confidence: 87%
“…Eight subjects (aged 24–67 y, three females) without known brain abnormalities were recruited. MT‐DICE imaging was performed in an oblique transverse orientation with the following imaging parameters: field‐of‐view (FOV) = 216 × 216 × 128 mm 3 , spatial resolution = 1.5 × 1.5 × 4.0 mm 3 , pulse TR = 19.30 ms, TEs = 2.46/4.92/7.38/9.84/12.30/17.22 ms (which is enough to generate relatively accurate T2*$$ {\mathrm{T}}_2^{\ast } $$ maps, according to 36 and our pilot study shown in Supporting Information Appendix S1, Section C), SR period (the temporal resolution of dynamic T1false/T2*$$ {\mathrm{T}}_1/{\mathrm{T}}_2^{\ast } $$ mapping) is approximately 1.2 s, containing 60 segments at time points varying from 19.30 to 1160 ms, flip angle = 10°, total time = 7.6 min. Single dose (0.1 mmol/kg of body weight) of CA (Gadavist; Bayer Schering Pharma, Berlin, Germany) was administered through antecubital intravenous access 1.5 min into the scan at the rate of 3.0 mL/s, followed by a 20 mL saline flush at the same rate.…”
Section: Methodsmentioning
confidence: 99%
“…Constant TR Multitasking using multi-echo readouts and a constant TR for both training and imaging data has been recently presented for T 2 * mapping in the brain 30 and T 2 */FF mapping in the liver. 31 The VTR approach proposed in this work clearly outperformed the CTR approach in motion phantoms and in the heart, as shown in Figure 3 and Supporting Information Figures S4 and S5.…”
Section: Discussionmentioning
confidence: 99%
“…Two interleaved data sets are collected during the continuous acquisition: The training data (dtr$$ {\mathbf{d}}_{\mathrm{tr}} $$) are frequently collected at k‐space center (0° radial spoke) to provide temporal information, and the imaging data (dimg$$ {\mathbf{d}}_{\mathrm{img}} $$) are collected with golden‐angle radial trajectory to provide spatial information. In previous MR Multitasking work for T 2 * mapping, 30,31 multi‐echo readouts were used for both training and imaging data (Figure 1B), which limited the temporal resolution and imaging efficiency. To achieve a higher temporal resolution to characterize cardiac motion, instead of using constant T R (CTR) for both datasets, a VTR scheme was developed in this work, in which the training data are collected using a single‐echo, short T R readout and imaging data are collected using a multi‐echo, long T R readout (Figure 1C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation